Antimalarial activity of the bisquinoline trans-N1,N2-bis (7-chloroquinolin-4-yl)cyclohexane-1,2-diamine: comparison of two stereoisomers and detailed evaluation of the S,S enantiomer, Ro 47-7737. - Ridley, R G (1997)
The S,S enantiomer of the bisquinoline trans-N1,N2-bis(7-chloroquinolin-4-yl)cyclohexane-1,2-diamine, Ro 47-7737, is significantly more potent against chloroquine-resistant Plasmodium falciparum than the R,R enantiomer and the previously described racemate. Both the enantiomers and the racemate are more potent inhibitors of heme polymerization than chloroquine, and their activities are probably mediated by inhibition of this parasite-specific process. The S,S enantiomer, Ro 47-7737, was studied in more detail and proved to be a potent antimalarial in the treatment of P. vivax ex vivo and P. berghei in vivo. Its suppression of P. berghei growth in a mouse model (50% effective dose, 2.3 mg/kg of body weight) was equal to that of chloroquine and mefloquine, and Ro 47-7737 was found to be more potent than these two drugs in the Rane test, in which the curative effect of a single dose is monitored. The dose at which 50% of animals were permanently cured (34 mg/kg) was markedly superior to those of chloroquine (285 mg/kg) and mefloquine (> 250 mg/kg). When administered orally at 50 mg/kg, Ro 47-7737 also showed a faster clearance of parasites than either chloroquine or mefloquine, and unlike the other two compounds, Ro 47-7737 showed no recrudescence. In a study to compare prophylactic efficacies of oral doses of 50 mg/kg, Ro 47-7737 provided protection for 14 days compared to 3 days for mefloquine and 1 day for chloroquine. The good curative and prophylactic properties of the compound can be explained in part by its long terminal half-life. The ability to generate parasite resistance to Ro 47-7737 was also assessed. With a rodent model, resistance could be generated over eight passages. This rate of resistance generation is comparable to that of mefloquine, which has proved to be an effective antimalarial for many years. Toxicity liabilities, however, ruled out this compound as a candidate for drug development.